THE INTEGRATION OF THE POLISH AGRICULTURE WITH THE EU IN OPINION OF FARMERS FROM THE MAŁOPOLSKA PROVINCE - Kachel, Barbara (Acta Scientiarum Polonorum. Oeconomia, 2002)
Summary. The integration of the Polish agriculture with the EU in opinion of farmers from the Małopolska province. The aim of the paper is to present the actual state of knowledge on integration of Polish agriculture with the European community prepared on the basis of questionnaire studies. The article also deals with economy of investigated farms and presents the opinions of farmers concerning advantages, threats and anxieties appearing from the future accession and from the necessary adjustments to the requirements of the EU. The farmers’ moods are rather pessimistic, they feel misinformed and generally are against the integration.